Senior tourists’ motivations for visiting cultural destinations: A cluster approach - Parreira, A.; Pestana, M. H.; Santos, J. A. C.; Fernández-Gámez, M. (Anatolia, 2021)
This study sought to contribute to the existing knowledge of consumer psychology regarding senior tourism in cultural destinations by improving the existing understanding of seniors’ motivations and related psychological processes. The research objectives were to outline a model of senior tourists’ push and pull motivations, which includes their emotions and satisfaction in cultural destinations; to understand the selection process of tourist attractions and activities in these destinations; and to identify clusters of seniors based on their emotions and level of satisfaction during visits. A theoretical model was created to analyse motivations and travel factors. The data collected facilitated the identification of four senior tourist clusters based on sociodemographic and psychographic differences. Various theoretical and managerial implications are presented.